1999
DOI: 10.1002/(sici)1521-3803(19990601)43:3<196::aid-food196>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Intraluminal immunoreactive caseinomacropeptide after milk protein ingestion in humans

Abstract: Caseinomacropeptide (CMP)is a 64 amino acids peptide which is the first product released after kappa-casein hydrolysis. The present work investigates the kinetics delivery of CMP in human jejunal lumen during the digestion of intrinsically [15N]-labelled casein, whey protein, yoghurt and pea flour meal. Effluents were collected through a nasointestinal tube and analysed for the enrichment in [15N] to evaluate the dietary nitrogen fraction. Detection and quantification of CMP was performed by an inhibition Elis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…The peptide released by natural digestion of casein in the stomach, with chymosin, CMP (11) has been shown to substantially inhibit the adherence of Streptococcus mutans to salivary pellicle (17,21,25,26), and this has been proposed to be the mechanism of anticariogenicity of milk protein fractions in animal caries models (7). In this study we have shown that CMP has growth-inhibitory activity against S. mutans and P. gingivalis as well as E. coli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peptide released by natural digestion of casein in the stomach, with chymosin, CMP (11) has been shown to substantially inhibit the adherence of Streptococcus mutans to salivary pellicle (17,21,25,26), and this has been proposed to be the mechanism of anticariogenicity of milk protein fractions in animal caries models (7). In this study we have shown that CMP has growth-inhibitory activity against S. mutans and P. gingivalis as well as E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that S. mutans will grow at pH 7.0 but not at lower pH values in the presence of the ionophore gramicidin, which collapses transmembrane cation gradients through formation of an anionic pore (3). CMP has been detected in the stomach, duodenum, and jejunum of humans after milk ingestion (11). The release of kappacin in the stomach therefore may be a mechanism to limit gastrointestinal tract infection in the developing neonate, by increasing the sensitivity of bacteria to gastric acid by collapsing essential transmembrane cation gradients.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have mainly relied on immunoreactive techniques (e.g., enzyme-linked immunoassay -ELISA) or Edman degradation of the Nterminal amino acids linked to peptide sequencers to identify positive peptide candidates. [5][6][7] However, advances in mass spectrometric (MS) analysis have allowed greater capability in the identication of peptides within complex mixtures and also identication of a large number of peptide sequences in an automated manner, for reviews, see: ref. [8][9][10][11].…”
Section: Richard (Dick) J Fitzgerald Is a Professor In The Life Sciementioning
confidence: 99%
“…It constitutes approximately 20% of the whey protein fraction and is resistant to acid [7,8]. It constitutes approximately 20% of the whey protein fraction and is resistant to acid [7,8].…”
Section: Introductionmentioning
confidence: 99%